The role of epigenetics in women’s reproductive health: the impact of environmental factors - Yu, Xinru; Xu, Jiawei; Song, Bihan; Zhu, Runhe; Liu, Jiaxin; Liu, Yi Fan; Ma, Ying Jie (Frontiers in Endocrinology, 2024)
This paper explores the significant role of epigenetics in women's reproductive health, focusing on the impact of environmental factors. It highlights the crucial link between epigenetic modificationssuch as DNA methylation and histones post-translational modificationsand reproductive health issues, including infertility and pregnancy complications. The paper reviews the influence of pollutants like PM2.5, heavy metals, and endocrine disruptors on gene expression through epigenetic mechanisms, emphasizing the need for understanding how dietary, lifestyle choices, and exposure to chemicals affect gene expression and reproductive health. Future research directions include deeper investigation into epigenetics in female reproductive health and leveraging gene editing to mitigate epigenetic changes for improving IVF success rates and managing reproductive disorders.